Exploring the wheat virome using high-throughput Nanopore sequencing: a metagenomic and phylogenetic analysis - Ranabhat, Nar Bahadur (Kansas State University, 2022)
Kansas is one of the top wheat-producing states in the United States. Many wheat viruses have been recognized as common yield-reducing factors. The synergistic impact of several concurrent infecting wheat viruses is responsible for millions of dollars lost in wheat production. Genetic resistance, using virus-resistant cultivars, is one of the key management practices of wheat viruses. The primary threat to durable genetic resistance is the presence of potential new virus variants in the field. The main objective of this study was to explore the field wheat virus population. We used the high-throughput Oxford Nanopore sequencing technique (ONT) to study the wheat virome. A survey was conducted in 2019, 2020, and 2021 in major wheat-growing counties of Kansas, and wheat leaves showing virus-like symptoms were collected. Total RNA was extracted, and cDNA sequencing libraries were made using the PCR-cDNA barcoding kit and loaded into ONT MinION flow cells. Sequencing reads were aligned to cereal virus references. We identified eight wheat viruses belonging to the genera: Tritimovirus, Poacevirus, Emaravirus, Bromovirus, Luteovirus, Polerovirus, Bymovirus, and Furovirus. We recorded mixed infections of two to five viruses in a single sample. Wheat streak mosaic virus (WSMV) + triticum mosaic virus (TriMV) mixed infection was the most predominant infection (16.7%), followed by WSMV + TriMV + brome mosaic virus (BMV) (11.9%) and WSMV single infection (11.9%). Phylogenetic analysis of the whole genomes of WSMV revealed the wide distribution of isolates into clades and subclades including European isolate. Potential WSMV recombinant isolates were found. BMV was identified for the first time in Kansas wheat. We used genetic and evolutionary approaches to characterize BMV isolates. On average, US BMV isolates showed low divergence. Coding regions of all BMV RNAs were under purifying or negative selection pressure. The whole-genome sequences of multiple isolates of High Plains wheat mosaic emaravirus and soilborne wheat mosaic virus were characterized. Additionally, virus viability in the inoculum over time was determined, and the relation of viral load and phenotypic symptoms were established, which assists in unbiased disease assessment in wheat virus varietal screening nurseries. Overall, the knowledge of the complexity of host-virus interactions, information of genetic variability, the phylogenetic relationship among isolates, and reports of new isolates of viruses and their co-infections will help in recommendation for sustainable management practices for wheat viruses.
Keywords: Wheat; Virus; Virome; Nanopore sequencing; Metagenomic; Phylogeny